Analysis of Factors Influencing the Demand for Online Ojek Transportation (Go-Jek) in Cirebon City - Anisa Kusmawarni; Abdul Nasir (Cirebon International Journal of Economics and Business, 2023)
With the increasing number of public transportation users in Indonesia and accompanied by increasingly sophisticated technology, communication and information facilities, it makes it easier for people in all activities. The existence of online motorcycle taxi transportation makes it very easy for the public. This study aims to determine the benefits of online transportation in digital and analyze the factors that affect the demand for online motorcycle taxis (go-jek) in Cirebon City. The method used in this study is descriptive qualitative. The results of this study are that there are several benefits of online transportation in the digital world, such as streamlining time, being safer and facilitating transactions. Then several factors that affect the demand for online motorcycle taxis (Go-jek) in the city of Cirebon are price, income, promotion and service quality.